1999
DOI: 10.1093/bja/83.6.933
|View full text |Cite
|
Sign up to set email alerts
|

Antiemetic prophylaxis in cardiac surgery: comparison of metoclopramide and ondansetron

Abstract: We have compared the effectiveness of ondansetron (115 patients) and metoclopramide (101 patients) for prevention of postoperative nausea and vomiting in patients undergoing cardiac surgery involving cardiopulmonary bypass. In a prospective, randomized, controlled, double-blind study, patients received oral ondansetron 16 mg or oral metoclopramide 10 mg, 1-2 h before surgery. Anaesthesia was not standardized. Assessments of the severity of nausea and occurrence of vomiting were made at intervals after extubati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 6 publications
3
16
0
2
Order By: Relevance
“…Some authors reported on a lower antiemetic potency of metoclopramide compared with the 5-HT 3 antagonists ondansetron and granisetron, respectively [26±28]. Others found no advantage of 5-HT 3 antagonists compared with metoclopramide [21]. In our study, by administrating 50 mg dolasetron, PONV was decreased signi®cantly compared with metoclopramide and placebo.…”
Section: Discussionsupporting
confidence: 44%
“…Some authors reported on a lower antiemetic potency of metoclopramide compared with the 5-HT 3 antagonists ondansetron and granisetron, respectively [26±28]. Others found no advantage of 5-HT 3 antagonists compared with metoclopramide [21]. In our study, by administrating 50 mg dolasetron, PONV was decreased signi®cantly compared with metoclopramide and placebo.…”
Section: Discussionsupporting
confidence: 44%
“…The control of emesis by the administration of antiemetic drugs when necessary after extubation in our practice may be the cause of not noticing any extrapyramidal symptoms or any other adverse reaction of metoclopramide or ondansetron. The previous study by Grebenik and Allman [7] and Woodwarg et al [8] have previously reported a 46-49% incidence of nausea and 37-42% incidence of vomiting in their patients after cardiac surgery. In our study, the incidence of PONV was considerably lower in comparison with their study.…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising, because PONV is more common during gynaecological surgery than most other surgeries [19]. In many placebo‐controlled studies, an antiemetic effect of metoclopramide was shown [20–23]. But in an overview, Rowbotham reported that low‐dose metoclopramide (5–10 mg), when it was given as premedication or given with induction of anaesthesia, was ineffective in prevention of PONV [24].…”
Section: Discussionmentioning
confidence: 99%